Interferon alpha (IFN-alpha) in treatment of malignant diseases - Jereb, Berta (Radiology and oncology (Ljubljana), 1997)
There are several natural varieties of IFN-alpha in clinical use. Although IFNs were the first cytokines in use as a new treatment modality, we still know little about their mode of action in malignancies. IFN-alpha can inhibit cell growth, but it has been shown only recently, on malignant cells from patients with multiple myeloma, that IFN-alpha can exert a direct cytotoxic effect on tumor cells. The treatment with natural leucocyte IFN-alpha in dosesused in the early clinical trials, are still most widely used. It has been shown that through a high local concentration by local application in malignant melanoma, basalioma, pleural carcinosis, glioblastoma, total local tumor control may be achieved. it is thys not known what the optimal doses of IFN-alpha are, and they may vary by the tumor type, as well as from patient topatient. The neccessary duration of treatment also remains an open question.IFNs are a tool for treatment of malignant tumors. Their cytotoxic effect, however, is not strong enough and does not last. At present, there is a vast field of investigative work stil open-but in the meantime it seems necessary to proceed with clinical trials of different types of IFN, the natural IFN-alpha again beeing the most interesting one.
Keywords: interferoni; onkologija; rak (medicina); zdravljenje